LEARNING FROM THE PAST: YOUTH EXPECTATIONS VS. YOUTH REALITY IN YUGOSLAVIA - Velkova, Angela (European Scientific Journal, ESJ, 2014)
During the 60’s and 70’s Yugoslavia dramatically increased their subcontracting relations with the West and thus changed the scope of industrialization that has been redesigned to mainly serve the production of export goods. Alongside a heavy reliance on foreign loans, Yugoslav leadership opted for educational reforms with the aim to: 1) create an abundant low- and semi-skilled workforce suitable for the labor intensive exports of semifinished goods 2) procure a voiceless and inert youth so that the preservation of the regime remained unquestioned and the leadership unchallenged. What is more, the inexistence of a genuine job market failed to identify the mismatch between the requirements of the labor demand and the profile of the labor supply which mainly consisted of unemployed youth between the age of eighteen and twenty five. The rising youth unemployment fomented a heavy family dependence that in turn bore critical implications in all socio-psychological aspects of youth development. The Yugoslav movie “Beach Guard in Winter” (1976) by Goran Pasjkaljevic and the character of Dragan powerfully resonate these and will be hereby used to illustrate the pervasive role of family in all domains of youth life. The work ultimately demonstrates that the mass-production of characters like Dragan in the 70’s and the 80’s proved detrimental to the transformation process of Yugoslav successor states in the 90’s and, at the same time, calls for learning the lessons from the past so that economic and political freefalls are avoided in the future.